2022
DOI: 10.1097/bpo.0000000000002333
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Head Deformity Associated With Hip Displacement in Nonambulatory Cerebral Palsy: Results at Skeletal Maturity

Abstract: Background: Maintaining femoral head shape (FHS) and acetabular sphericity are important goals in preventing long-term osteoarthritis in hips in children with cerebral palsy (CP). As acetabular morphology has been widely studied, our objective was to determine FHS in CP after triradiate cartilage (TRC) closure, a proxy for skeletal maturity, and the risk factors associated with residual deformity and osteoarthritis. Methods: In this retrospective cohort study, patients with CP [Gross Motor Function Classific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…A recent study of non-ambulant children with CP investigated the status of femoral head deformity at skeletal maturity, finding an MP > 30% at triradiate cartilage closure was associated with a ‘more severe’ outcome at final follow-up [ 76 ]. This more severe head shape was also associated with a higher risk of worse osteoarthritis by Tönnis grading.…”
Section: Femoral Head Deformity: Salvage or Reconstruction?mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of non-ambulant children with CP investigated the status of femoral head deformity at skeletal maturity, finding an MP > 30% at triradiate cartilage closure was associated with a ‘more severe’ outcome at final follow-up [ 76 ]. This more severe head shape was also associated with a higher risk of worse osteoarthritis by Tönnis grading.…”
Section: Femoral Head Deformity: Salvage or Reconstruction?mentioning
confidence: 99%
“…Interestingly, the authors found that prior reconstructive surgery had no impact on head shape at skeletal maturity which they felt was likely due to a lack of complete containment of the femoral epiphysis. Additional work is required to precisely define the degree of femoral head deformity which is amendable to reconstructive surgery versus the degree of deformity which would be better managed by a salvage surgical option [ 45 , 76 ].…”
Section: Femoral Head Deformity: Salvage or Reconstruction?mentioning
confidence: 99%
“…These patients merit continued surveillance after closure of the triradiate cartilage. In a similar study, the shape of the femoral head at skeletal maturity was found to be negatively affected when the migration percentage was ‡30.5% at the time of triradiate cartilage closure 25 . This was associated with worse osteoarthritis radiographically, although pain scores were not collected in this study.…”
Section: Neuromuscularmentioning
confidence: 78%
“…Although we have included information on the possible use of the classification in skeletally immature patients, the obtained results do not fully meet the expectations. Ulusaloglu et al [21] showed an increase in the number of type C and D femoral head shapes in older children with CP close to skeletal maturity. Observed changes can even progress after skeletal maturity.…”
Section: Discussionmentioning
confidence: 96%